Prevalence of influenza A infection in the Middle‐East: A systematic review and meta‐analysis. (15th February 2018) - Moghoofei, Mohsen; Monavari, Seyed Hamidreza; Mostafaei, Shayan; Hadifar, Shima; Ghasemi, Amir; Babaei, Farhad; Kavosi, Hoda; Tavakoli, Ahmad; Javanmard, Davod; Esghaei, Maryam; Khodabandehlou, Nilofar
Abstract: Objective: This systematic review and meta‐analysis was performed to determine the prevalence rate of influenza virus from different parts of Middle East region, and present an overall relative frequency (RF) for this region. Methods: The authors performed a systematic literature review from several reliable databases such as PubMed, ISI Web of Science and Scopus during 2000–2016. Furthermore, the keywords of this research were 'Influenza', 'Subtype', 'Seroprevalence', 'Incidence', 'Seroepidemiology', 'H1N1', 'H3N2', 'H5N1', 'H9N2', 'Middle‐East' and 'Meta‐analysis'. The reported data were selected according to inclusion and exclusion criteria. Results: The authors selected 71 studies out of 1147 for the present review. The overall estimation of the prevalence of influenza virus was 10.2% [95% confidence interval (CI): 10.1%–10.3%]. However, based on our records, the evident heterogeneity of influenza virus was observed among the studies (Cochran Q test, P value <.001 and I ‐squared = 100%). It should be noted that influenza virus infection's RF varied from 0.5% in Qatar to 70% in Syria. Conclusions: The results of this review are remarkable, they show that influenza infection RF is variable due to several factors. Thus, further researches should be taken to minimize the emergence and transmission of influenza virus.